An Old Pathogen in a New Environment–Implications of Coxiella burnetii in Australian Fur Seals (Arctocephalus pusillus doriferus) - Gardner, Brett R.; Stenos, John; Hufschmid, Jasmin; Arnould, John P. Y.; McIntosh, Rebecca R.; Tadepalli, Mythili; Tolpinrud, Anita; Marenda, Marc; Lynch, Michael; Stent, Andrew (Frontiers in Marine Science, 2022)
The Australian fur seal (Arctocephalus pusillus doriferus) has experienced a slower than expected population recovery since the end of the commercial sealing era, with a high third trimester abortion rate. There is currently no known proximate cause. Coxiella burnetii (Cb) is a well-known cause of abortion in domestic and wildlife species and an important zoonotic pathogen. It has been recorded from a small number of northern hemisphere marine mammals and may be a potential contributory factor to decreasing populations of northern fur seals (Callorhinus ursinus) and Steller sealions (Eumetopias jubatus). It has not been recorded from marine mammals in the southern hemisphere but is well documented in ruminants and wildlife in Australia as a cause of reproductive failure. Third trimester aborted fetuses (n = 46) and full-term placentas (n = 66) from Australian fur seals, were collected on Kanowna Island and Seal Rocks in Bass Strait, south-eastern Australia. Utilizing routine hematoxylin and eosin histopathology, Cb immunohistochemistry and two different qPCR targets–htpAB and com1, Cb was identified. Routine histopathology and immunohistochemistry were insensitive for the detection of Cb. The detected Cb prevalence ranged from 10.6% for com1 up to 40.9% with htpAB. Coxiella burnetti was readily detected in full-term placentas but in aborted fetal material only in a single placenta associated with a still birth. The exact significance is currently unclear, but this highlights that Cb is present in Australian fur seals, breeding in Bass Strait. Bass Strait is in one of the world’s fastest warming oceanic regions and marine mammals breeding in the area are likely to be key indicators of marine ecosystem stressors. This first description of Cb in a marine mammal from the southern hemisphere, highlights the need to further investigate the potential risks this pathogen poses to Australian fur seals and sympatric marine mammals. Additionally, it is important to determine the zoonotic risk of this pathogen to persons working with, and in proximity of, Australian fur seal breeding colonies.